Unveiling the dual-pathway effect of CSR perception environmental on employee pro-environmental behavior: evidence from Chinese marine enterprises - Duan, Xu; Wu, Jiangyue (Frontiers in Psychology, 2025)
To achieve the sustainable development goals and in response to the green development policies, many enterprises have actively incorporated corporate social responsibility (CSR) into their strategic plans in order to enhance environmental sustainability. This study explores the cognitive and emotional pathways through which perceived environmental CSR (PECSR) influences pro-environmental behavior (PEB) among employees in China’s marine enterprises, based on the Cognitive-Affective Personality System theory. The research was conducted through data collection and verified through the structural equation model. PECSR is significantly and positively associated with PEB, mediated by meaningful work and connectedness to nature, with a green psychological climate further supporting this relationship. Results highlight PECSR as a critical factor in CSR effectiveness. When planning sustainability strategies, enterprises should consider the significant impact of PECSR on employee behavior to foster environmentally responsible practices.